Development of source material for pea breeding through chemical mutagenesis and evaluation of its genetic diversity using SSR markers - K. P. Gainullina; B. R. Kuluev; F. A. Davletov (Труды по прикладной ботанике, генетике и селекции)
Background. Pea (Pisum sativum L.) is a valuable leguminous crop of worldwide importance. The main problem of modern plant breeding is a decrease in the genetic diversity of crops, including pea. One of the ways to increase genetic polymorphism is the use of chemically induced mutagenesis. Sodium azide (NaN3) is a highly effective chemical mutagen successfully used in mutation breeding to increase the productivity of cultivated plants and enrich them with new useful traits. We used it to obtain new pea breeding material.Materials and methods. Experiments were carried out to obtain pea mutants using sodium azide at the concentrations of 1, 5 and 10 mM and the exposure time of 3 and 9 h. Molecular genetic polymorphism of the М2 plants and the original cultivar was assessed using 10 SSR markers from the microsatellite genomic library (Agrogene®, France).Results. Optimal concentrations of sodium azide and the duration of seed treatment with it were identified: 1–5 mM for 3 h. Sixteen mutant populations were obtained; in ten of them a change in the leaf type was found. An analysis of the yield structure components revealed a significant superiority (p < 0.05) over the initial cultivar ‘Pamyati Khangildina’ in the mutant populations No. 1, No. 5, No. 9, No. 10, No. 15 and No. 16 in the number of seeds per pod, No. 9 and No. 16 in the weight of 1000 seeds, and No. 16 in the weight of seeds per plant. A dendrogram constructed on the basis of the SSR analysis data showed the degree of differences between the M2 populations of pea plants and the initial cultivar ‘Pamyati Khangildina’.Conclusion. The obtained mutant populations are planned to be used in pea breeding as sources of high seed numbers in pods, seed yield, seed weight per plant, and large seed size. A microsatellite analysis with 10 SSR markers revealed differences among the M2 mutant populations at the genetic level and made it possible to identify them.